The severity of depression is associated with pelvic inflammatory diseases: A cross-sectional study of the United States National Health and Nutrition Examinations from 2013 to 2018 - Huang, TianJiao; Cao, RenShuang; Liu, PengFei; Liu, JinXing; Yu, Xiao (Frontiers in Medicine, 2022)
Purpose As depression in patients with pelvic inflammatory diseases (PID) has received increasing attention in recent years, this study aims to investigate the relationship between depression severity and risk factors for pelvic inflammatory disease, and to provide new perspectives in the treatment of PID. Patients and methods Multivariate regression was used to evaluate the association between pelvic inflammatory disease and the severity of depression. Females who participated in the United States National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018 were included. In addition, risk factors for PID and depression were also included in the analysis as adjustment factors. Results The risk of developing PID was associated with depressive status (odds ratio, OR 1.10, 95% confidence interval, CI 1.08–1.12), especially in people with severe depression (odds ratio, OR 6.34, 95% confidence interval, CI 3.72–10.79). Subgroup analysis showed differences in the risk of PID among people with different characteristics. Conclusion This study showed that there may be a potential positive association between depressive status and the prevalence of PID in the United States adult female population. Depression should be actively looked for in all patients with PID and treated appropriately